(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study defines possible causes of failures in the application of software tools for data management at Gamal Abdel Nasser University of Conakry, including student grades and other related data. This would improve existing software tools, or failing that, create a more powerful tool. This is of principal significance to the university to better protect its highly sensitive data. Therefore, we analyzed some possible weaknesses in the data management methods of the university, but also tried to propose some preventive solutions. This point was also discussed by a few researchers including Katering and Trivedik [6], Lisnianski and Levitin [1], Herzig [18].